2014
DOI: 10.1080/0969594x.2014.975675
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel predictors of differing perceptions of Assessment for Learning practices between teachers and students

Abstract: Assessment for Learning (AfL), as a way to promote learning, requires a 'match' or a shared focus between student and teacher to be effective. But students and teachers may differ in their perceptions of the purpose and process of classroom assessment meant to promote learning. Perceptions regarding AfL practices in their classroom were collected from both teachers and students. Teacher efficacy for instructional strategies, student engagement, classroom management and student self-reported language proficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 59 publications
2
10
1
Order By: Relevance
“…Student perceptions of FA practices First of all, both the survey and focus group discussions showed that most secondary school students in our sample valued and considered their teacher's assessment and feedback practices to be formative, only when it was warm and friendly. This replicates results from previous studies (e.g., Pat-El et al, 2015;Weaver, 2006) that students value warm, supportive teacher feedback. However, according to Rach et al (2013) students' positive perceptions of teacher assessment practices do not necessarily result into effective performance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Student perceptions of FA practices First of all, both the survey and focus group discussions showed that most secondary school students in our sample valued and considered their teacher's assessment and feedback practices to be formative, only when it was warm and friendly. This replicates results from previous studies (e.g., Pat-El et al, 2015;Weaver, 2006) that students value warm, supportive teacher feedback. However, according to Rach et al (2013) students' positive perceptions of teacher assessment practices do not necessarily result into effective performance.…”
Section: Discussionsupporting
confidence: 89%
“…The impact of FA and AfL practices depends on whether students perceive and utilize the guidance provided by their teacher to improve their learning. The success of FA and AfL hinges on the student's willingness to engage in appropriate actions to close the gap between their actual performance and the target performance (Sadler, 1989) and whether students perceive and utilize the guidance provided by their teacher to improve their learning strategies (Pat-El, Tillema, Segers, & Vedder, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results seem to suggest that the students' perceptions of formative assessment are mediated by other factors possibly related to students' motivation, achievement, or teacher efficacy. A study by Pat-El, et al (2015) showed that differences in perceptions can be influenced by factors such as teacher efficacy and student language proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Significant research has been done regarding teacher's perceptions of formative assessment (Öz, 2014;Pat-El, et al, 2015;Nasr et al, 2018;Kyaruzi et al, 2018) but very limited focus on students' perceptions of formative assessment in secondary schools. Related research has looked at assessment in general.…”
Section: Introductionmentioning
confidence: 99%